Komposisi alga mikro dalam tasik buatan di kampus Unimas, Sarawak, Malaysia - Elora, binti Poukin. (Universiti Malaysia Sarawak (UNIMAS), 2005)
The study ojmicroalgae composition in man-made lake was conducted in UN/MAS campus, at Kota Samarahan, Sarawak. There are three lenthic freshwater lake chosen as the study sites and labeled A, Band C. The size range ojthe microalgae is between 2pm to 200pm. The abundance and distribution ojmicroalgae in the lakes are related to the composition ojwater quality especially nitrate (N03'-) and phosphate (POl). The result shows that members oj Chlorophyta division were abundance in the most ojlakes. There are Jour divisions from the eukaryotic was abundance in the lakes, namely; the genera from Chlorophyta are Pediastrum (5 species), Tetraedron (6 Species), Enchinosphaerella (l Species), Ankistrodesmus (3 Species), Scenedesmus (3 Species) and Chlamydomonas (2 Species). The genera from Euglenophyta are Phacus (4 Species), Lepocine/is (3 Species) and Trachelomonas (l Species). The genera from Pyrrhophyta are Glenodinium (4 Species) and Cystodinium (l Species). The genera from division oj Chrysophyta are Synedra (l Species) and Navicula (l Species). While the genera from the prokaryotic in the division